Creation of a Network to Promote Universal Screening for Lynch Syndrome: The Lynch Syndrome Screening Network - Mange, S. (J Genet Couns, 2014)
The Evaluation of Genomic Applications in Practice and Prevention Working Group published an evidence-based recommendation stating that every newly diagnosed colorectal cancer (CRC) should undergo tumor screening for Lynch syndrome (LS). In 2011, leading cancer institutions and public health agencies created the Lynch Syndrome Screening Network (LSSN) in order to promote routine LS screening on all newly diagnosed CRCs and endometrial cancers (EC). The LSSN facilitates implementation of appropriate screening via shared resources, protocols and data through network collaboration. The LSSN website contains resources for institutions interested in initiating screening, including materials for program development, implementation and sustainability. The LSSN listserv gives providers access to experts in LS screening and implementation. The LSSN database will allow exploration of key gaps in implementation as a consortia-wide endeavor. To date, the LSSN’s membership includes 85 institutions involved in the care of CRC patients and nine official partners such as national and state public health entities and other non-profit institutions. Nearly 80 % of the LSSN’s members have already implemented routine or universal CRC and/or EC screening. LSSN serves to further the population health potential of universal LS screening through collaborative efforts and resources.